5PSQ-091 Trifecta™ bioprostheses : evaluation of the safety based on the study of degenerations according to the varc-3 classification. Issue 1 (23rd March 2023) - Richez, O; Hun-Chabry, Y; Malaquin, D; Hudelo, J; Caus, T; Petit, A
Abstract : Background and Importance: In 2021, cardiologists reported to the medical-devices-vigilance sector serious incidents in four patients with a first-generation Trifecta™ bioprosthesis that resulted in three aortic valve replacement (AVR) and one death. The question of degeneration of their bioprosthesis arose. Aim and Objectives: The aim was to evaluate the intrinsic imputability of Trifecta™ for dysfunction in patients implanted and to reassess their referencing in our centre. Material and Methods: A retrospective, single-centre and observational study of computerised patient records (CPR) was conducted between 02/04/2011, date of our centre's first implantation, and 12/31/2016 to have 5 years of follow-up per patient. Trifecta™ valves and data related to the implantation were extracted from the traceability software. The collection of echographic and clinical follow-up data was based on the CPR with an extended follow-up period until 03/31/2022. Dysfunctions were classified according to the VARC-3 classification criteria : structural valve deterioration (SVD), non-structural valve dysfonction (NSVD), thrombosis and endocarditis. The study was approved by our local research department. Results: A total of 382 bioprostheses was implanted in 378 patients, mean age 73.0 years and 60.7% male. Data were missing for 253 bioprostheses and 15 patients died perioperatively. Among the 114 bioprostheses with conclusive data, 50 functionned properly (mean follow-up time of 6.6 years) and 64 presented dysfunctions : 34 SVD, 10 NSVD (8 paravalvular regurgitation, 2 prosthesis-patient mismatches) and 20 endocarditis. AVR occurred for 20 patients following SVD and for 11 patients following endocarditis (4 of whom had a second Trifecta™) within a mean time of 6.7 years and 3.4 years, respectively. Conclusion and Relevance: The classification of failures according to VARC-3 allowed us to confirm the intrinsic imputability of the Trifecta™ bioprostheses regarding to the number of SVD-type dysfunctions. Although this study has limitations, it shows the understatement of medical-devices-vigilance cases by the medical staff. The 64 files with dysfunstions will be transmitted to the natonal health autority. The patients will be reviewed to complete the data and perform an echographic follow-up. According to the manufacturer, degenerations could be related to the expansion system that was improved in the second-generation Trifecta™ marketed in 2016. Since this study, the Trifecta™ has been removed from the hospital formulary. References and/or Acknowledgements: Conflict of Interest: No conflict of interest